Review of the pharmacokinetics of French maritime pine bark extract (Pycnogenol®) in humans - Bayer, Jasmin; Högger, Petra (Frontiers in Nutrition, 2024)
The French maritime pine bark extract Pycnogenol ® is a proprietary product from Pinus pinaster Aiton. It complies with the quality specifications in the United States Pharmacopeia monograph "Pine extract" in the section of dietary supplements. Pycnogenol ® is standardized to contain 65-75% procyanidins which are a variety of biopolymers consisting of catechin and epicatechin monomeric units. The effects of Pycnogenol ® have been researched in a multitude of human studies. The basis for any in vivo activity is the bioavailability of constituents and metabolites of the extract. General principles of compound absorption, distribution, metabolism and elimination as well as specific data from studies with Pycnogenol ® are summarized and discussed in this review.Based on plasma concentration profiles it can be concluded that low molecular weight constituents of the extract, such as catechin, caffeic and ferulic acid, taxifolin are readily absorbed from the small intestine into systemic circulation. Procyanidin oligomers and polymers are subjected to gut microbial degradation in the large intestine yielding small bioavailable metabolites such as 5-(3',4'dihydroxyphenyl)--valerolactone. After intake of Pycnogenol ® , constituents and metabolites have been also detected in blood cells, synovial fluid and saliva indicating a substantial distribution in compartments other than serum. In studies simultaneously investigating concentrations in different specimen, a preferential distribution of individual compounds has been observed, e.g. of ferulic acid and 5-(3',4'-dihydroxyphenyl)--valerolactone into synovial fluid compared to serum. The main route of elimination of constituents and metabolites of the French pine bark extract is the renal excretion.The broad knowledge accumulated regarding the pharmacokinetics of compounds and metabolites of Pycnogenol ® constitute a rational basis for effects characterized on a cellular level and observed in human clinical studies.